2009
DOI: 10.1002/acp.1564
|View full text |Cite
|
Sign up to set email alerts
|

Do human figure diagrams help alleged victims of sexual abuse provide elaborate and clear accounts of physical contact with alleged perpetrators?

Abstract: The present study examined whether the use of human figure diagrams within a well-structured interview was associated with more elaborate and clearer accounts about physical contact that had occurred in the course of an alleged abuse. The sample included investigative interviews of 88 children ranging from 4 to 13 years of age. Children were interviewed using the NICHD Investigative Interview Protocol, and were then asked a series of questions in association with unclothed gender-neutral outline diagrams of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
2
22
1
1
Order By: Relevance
“…In investigative interviews, adding diagram-assisted questions after other questions does lead children to recall additional information (e.g., Aldridge et al, 2004), including elaborations of bodily contact (Teoh, Yang, Lamb, & Larsson, 2010), but the accuracy of this information and the reason children recall more (i.e., diagrams vs. additional retrieval attempts vs. more specific questions) are unclear. Controlled laboratory studies that provide accuracy assessments do not support the use of body diagrams to elicit disclosures.…”
Section: Body Diagramsmentioning
confidence: 99%
“…In investigative interviews, adding diagram-assisted questions after other questions does lead children to recall additional information (e.g., Aldridge et al, 2004), including elaborations of bodily contact (Teoh, Yang, Lamb, & Larsson, 2010), but the accuracy of this information and the reason children recall more (i.e., diagrams vs. additional retrieval attempts vs. more specific questions) are unclear. Controlled laboratory studies that provide accuracy assessments do not support the use of body diagrams to elicit disclosures.…”
Section: Body Diagramsmentioning
confidence: 99%
“…However, since the accuracy (i.e. total correct reported information divided by the total correct and incorrect information) of this information could not be measured, this result needs to be interpreted with caution (see also Teoh, Yang, Lamb, & Larsson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is of practical significance as children are often interrogated weeks or months after a traumatic event (see Bruck, 2009). Finally, there is little research examining the effect of age on the use of HFDs on children's recall (see Aldridge et al, 2004;Teoh et al, 2010). The above described studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, we know very little about how children report touches in the context of sexual abuse. Teoh, Yang, Lamb, and Larsson (2010) found that alleged victims of sexual abuse were generally able to describe the body parts that had been touched clearly but that younger children often failed to provide information indicating the severity of the abuse. In the present study, we focused specifically on children and interviewers' use of the word "touch" when talking about the alleged sexual abuse.…”
Section: Abstract Investigative Interviewing Bodily Contact Touchinmentioning
confidence: 96%